2018
DOI: 10.3892/etm.2018.6376
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokine expression in patients with sepsis at an intensive care unit

Abstract: Abstract. Sepsis is a systemic inflammatory response syndrome caused by infection of bacteria, fungi and/or viruses in clinical patients. It is known that inflammatory cytokine levels have an essential role in the progression of sepsis. The present study investigated the role of inflammatory markers in human peripheral blood mononuclear cells (hPBMCs) of patients with sepsis at an intensive care unit. In addition, the plasma levels of inflammatory cytokines were compared between sepsis patients and healthy ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
0
19
0
2
Order By: Relevance
“…The corticosteroid budesonide has been found to reduce TNFα secretion from macrophages in vitro by approximately 40% at a similar dose of 1 nM [35]. Additionally, it has been found that serum levels of IL-1β and TNFα are only 45%–50% lower in healthy patients than those hospitalized with sepsis [36]. As such, we suggest that our results would translate in vivo to a measured yet significant physiological effect to reduce damaging inflammation in lung disease, without compromising the necessary healing response of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The corticosteroid budesonide has been found to reduce TNFα secretion from macrophages in vitro by approximately 40% at a similar dose of 1 nM [35]. Additionally, it has been found that serum levels of IL-1β and TNFα are only 45%–50% lower in healthy patients than those hospitalized with sepsis [36]. As such, we suggest that our results would translate in vivo to a measured yet significant physiological effect to reduce damaging inflammation in lung disease, without compromising the necessary healing response of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…A notorious example is a highly virulent methicillin-resistant S. aureus strain PVL(+)MRSA that elaborates various toxins including the multimeric pore forming toxin Panton-Valentine leukocidin. Cytokine storm in bacterial sepsis includes a release of an array of inflammatory cytokines (68,69) combined with impaired glucose tolerance (70). Curiously, adipose-derived hormone leptin becomes a pathogen in sepsis and exacerbates sepsismediated morbidity and mortality (71).…”
Section: Dea Inhibited Virulence Factors Multidrug Resistant Staphylococcus Aureus In Human Pbmcs and In An In Vivo Model Of Bacterial Sementioning
confidence: 99%
“…Sepsis is a systemic inflammatory response syndrome, which is triggered by infection with pathogenic bacteria, viruses or fungi. 1 In severe septic patients, multi-organ dysfunction is the major cause of death. 2 Acute lung injury (ALI), one of the most common severe sepsis complications, is a syndrome of severe acute respiratory failure.…”
Section: Introductionmentioning
confidence: 99%